Experimental and DFT studies of WO3–CuO p-n heterojunctions for enhanced photoelectrochemical performance. (September 2022) - Li, Jingjing; Guo, Chenpeng; Li, Lihua; Gu, Yongjun; BoK-Hee, Kim; Huang, Jinliang
Abstract: The WO3 –CuO p-n heterojunction array photoelectrodes on FTO substrate were fabricated via hydrothermal and electrochemical deposition method. The effect of CuO loading on the photoelectrochemical performance of the WO3 –CuO heterojunctions was investigated by controlling the electrodeposition time. The obtained WO3 –CuO heterojunctions broaden the range of light absorption and improved the charge carrier separation efficiency. The optimum WO3 –CuO heterojunction photoelectrodes exhibit 4.5 times higher photocurrent density than that of WO3 nanorod. Density functional theory calculations demonstrate that the interfacial interaction can effectively regulate the electronic structure and decrease the overpotential, which improve the charge separation efficiency and enhance the photoelectrochemical performance. This work provides a promising approach for the design of highly efficient heterostructures in PEC water splitting applications. Graphical abstract: The p-n heterojunctions WO3 –CuO have been fabricated via the hydrothermal and electrodeposition method. Charge carrier separation and transport were significantly improved after fabricating WO3 –CuO heterojunctions, thus enhancing the performance of photoelectrochemical. Image 1 Highlights: The p-n heterojunctions WO3 –CuO have been fabricated. CuO nanoparticles as light absorber enhanced the light absorption efficiency. The WO3 –CuO heterojunction promote charge separation and transfer. WO3 –CuO heterojunction photoanode exhibited efficient PEC performance.